The learning curve how business schools are re-inventing education - Iñiguez de Onzoño, Santiago (Palgrave Macmillan, 2011)
"How do you create world-class educational institutions that are academically rigorous and vocationally relevant? Are business schools the blueprint for institutions of the future, oran educational experiment gone wrong?This is thefirst title in a new series from IE Business School,IE Business Publishing"-- Provided by publisher.